IDENTIFIKASI SENYAWA ANTIDIABETES SECARA in Silico PADA Carica pubescens Lenne & K. Koch - Ainun Nikmati Laily; Ahmad Nuruddin Khoiri (El-Hayah, 2016)
Carica pubescens Lenne K. Koch is one of the typical highland crops in Indonesia. This plant can be found in the region of Cangar and Bromo in East Java, as well as the Dieng Plateau, Central Java Wonosobo-Banjarnegara. Morphological, chemical content, and analysis of protein banding pattern of the Carica pubescens has been done, but more about the use of active compounds for pharmaceutical raw materials, in Diabetes Mellitus type 2 have not been studied. One therapeutic approach to lowering blood sugar levels posprandial is to slow down or inhibit the absorption of glucose through inhibition of the carbohydrates hidrolitic enzyme such as α-amylase and α-glucosidase. This study aims to identify antidiabetic compounds in silico. Antidiabetic compounds were analyzed by methods of docking. The results showed that papain and cysteine protease in C. pubescens have better binding affinity to α-amylase and α-glucosidase compared to iridoid glycosides. Papain and cysteine proteases isolated from C. pubescens are potential to be developed as an antidiabetic.